2007
DOI: 10.1007/s10453-006-9039-6
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on the airborne fungi in Athens, Greece, by viable and non-viable sampling methods

Abstract: Airborne fungi were studied in the city of Athens using two complementary methods in which 136 concurrent samplings were carried out during the 12-month period from January until December 1998. A portable Burkard air sampler for agar plates was used for trapping the culturable portion of the mycobiota. Nineteen genera of fungi were identified and assessed in terms of total numbers and fluctuations in , Trichoderma and Ulocladium), with the exception of those included in the Sphaeropsidales, the yeasts, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 22 publications
6
23
0
4
Order By: Relevance
“…The occurrence of the maximum concentration in July corresponds to the results broadly demonstrated by other studies on the subject: the growth of fungal species is favoured by high levels of relative humidity and air temperature range 18-32˚C, parameters which are often observed during the summer season in our region (Herrero et al, 1996;Pelizzari, 1996;Munuera et al, 2001;Pyrri & Kapsanaki-Gotsi, 2007).…”
Section: Resultssupporting
confidence: 88%
“…The occurrence of the maximum concentration in July corresponds to the results broadly demonstrated by other studies on the subject: the growth of fungal species is favoured by high levels of relative humidity and air temperature range 18-32˚C, parameters which are often observed during the summer season in our region (Herrero et al, 1996;Pelizzari, 1996;Munuera et al, 2001;Pyrri & Kapsanaki-Gotsi, 2007).…”
Section: Resultssupporting
confidence: 88%
“…The seasonality of sporulation observed in taxa like Alternaria, Cladosporium, Penicillium, and others support this hypothesis (i.e. Garrett et al 1997;Henriquez et al 2001;Stennett et al 2004;Pyrri et al 2007;Oliveira et al 2009). The spores of these fungi achieve their highest aerial concentrations in the spring and/or fall at locations where rains and mild temperatures, adequate for fungal growth, occur in these seasons.…”
Section: Are Grasses An Important Source Of Airborne Spores?supporting
confidence: 61%
“…Quintero et al (2010) suggested that the concentration of fungal spores in the atmosphere of Puerto Rico is increased from August to September. However, the comparison of aerobiological results is very difficult due to geographical, meteorological, and biological differences between the areas that are studied, as well as the impact of humans on ecosystems (Randon et al 2002;Pyrri and Kapsanaki-Gosti 2007). These results could also be affecting the wind speed, variable not recorded in this work and as the temperature and relative air humidity can vary from year to year (Agrios 2005).…”
Section: Discussionmentioning
confidence: 77%